Vaccine hesitancy: a major hurdle even among women healthcare workers - Kamath, Anusha; Yadav, Anita; Baghel, Jyoti; Mundle, Shuchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: One of the major threats to the COVID-19 vaccines rollout and successful mitigation of the pandemic is vaccine hesitancy. Vaccine hesitancy refers to delay in acceptance or refusal of vaccination despite availability of vaccination services. The COVID-19 vaccine trials generated very limited data on safety and efficacy for pregnant women and children, since pregnant women were not included in any of the phase I/II or III trials. Hence the authors made an attempt to understand vaccine hesitancy among women healthcare and frontline workers with a focus on vaccination during pregnancy and lactation. Methods: The recruitment of participants was done by purposive snowballing technique over a period of 15 days. The data collection was done through an online questionnaire generated with the help of Google forms. After excluding women who exceeded the age criteria and incompletely filled questionnaires, 101 responses were considered for analysis. Data analysis was done using SPSS software version 22. Results: From a total of 101 responses for analysis, 26% had comorbidities. Of the 9 women who were pregnant, majority was in the second trimester (55.6%). Majority of the women, 63.6% had been feeding for more than six months. Of the respondents who had refused vaccination, most wanted to wait longer for further research on safety and efficacy (47.8%). Conclusions: The reasons for pregnant women to decline COVID-19 vaccination during pregnancy even if the vaccine were safe and free were that they did not want to expose their developing baby to any possible harmful side effects, would like to see more safety data among pregnant women and unclear recommendations from the healthcare provider. As HCWs are envoys for evidence based medical interventions, and they are critical in promoting vaccine acceptance amongst the general population, it is important to design effective strategies to improve vaccine acceptance amongst this population.